Factors influencing the accuracy of non-invasive blood pressure measurements in patients admitted for cardiogenic shock - Seidlerová, Jitka; Tůmová, Pavlína; Rokyta, Richard; Hromadka, Milan (BMC cardiovascular disorders, 2019)
BACKGROUND: Although invasively measured blood pressure (invBP) is regarded as a "gold standard" in critically ill cardiac patients, the non-invasive BP is still widely used, at least at the initiation of medical care. The erroneous interpretation of BP can lead to clinical errors. We therefore investigated the agreement of both methods with respect to some common clinical situation. METHODS: We included 85 patients hospitalized for cardiogenic shock. We measured BP every 6 h for the first 72 h of hospitalization, in all patients. Each set of BP measurements included two invasive (invBP), two auscultatory (auscBP), and two oscillometric (oscBP) BP measurements. InvBP was considered as a gold standard. Mean non-invasive arterial pressure (MAP) was calculated as (diastolic pressure + (pulse pressure ÷ 3)). We used Bland-Altman analysis and we calculated concordance correlation coefficients to assess agreement between different BP methods. RESULTS: We obtained 967 sets of BP measurements. AuscMAP and oscMAP were on average only 0.4 ± 8.2 and 1.8 ± 8.5 mmHg higher than invMAP, respectively. On the other hand, auscSBP and oscSBP were on average - 6.1 ± 11.4 and - 4.1 ± 9.8 mmHg lower than invSBP, respectively. However, the mean differences and variability for systolic and diastolic BP variability were large; the 2 standard deviation differences were ± 24 and 18 mmHg. In hypotension, non-invasive BP tended to be higher than invBP while the opposite was true for high BP values. Clinical conditions associated with hypotension generally worsened the accuracy of non-invasive MAP. CONCLUSIONS: Mean arterial pressure measured non-invasively appears to be in good agreement with invasive MAP in patients admitted for cardiogenic shock. Several clinical associated with hypotension can affect accuracy of non-invasive measurement. Auscultatory and oscillometric measurements had similar accuracy even in patients with arrhythmia.
Keywords: poslech; Male; Patient Admission; Oscillometry; Aged; Prospective Studies; mužské pohlaví; senioři; měření krevního tlaku; kardiogenní šok; reprodukovatelnost výsledků; Shock, Cardiogenic; příjem pacientů; Reproducibility of Results; Arterial Pressure; Auscultation; Time Factors; arteriální tlak; lidé; ženské pohlaví; oscilometrie; Humans; časové faktory; prediktivní hodnota testů; Female; lidé středního věku; Blood Pressure Determination; Predictive Value of Tests; Middle Aged; prospektivní studie